Computational intelligence for cash flow planning - Su Yadana Zaw (2014)
Computational Intelligence for Cash Flow Planning is a computational tool for decision making support for choosing financial investments using a famous evolutionary algorithm called genetic algorithm. Genetic algorithm (GA) is applied for selecting of high quality stocks with investment value. The Genetic Algorithm will identify stocks that have excess return and the potential to outperform the market using the fundamental financial and price information of stocks trading.